Redução do desperdício de alimentos: estudo em um restaurante universitário - Zanini, Marco Antonio (2013)
The world food production is more than enough to meet the needs of the entire population of the earth, but the losses in the different production stages and the preparation and consumption make this amount produced becomes inadequate. In a hungry world in which we live, any food waste could mean the end of all human life. Although the harvesting techniques and logistics are constantly enhanced, and the quantity and quality of food prepared in homes and restaurants, the waste is still large. Restaurants should prepare only what you need and customers should not serve in excess. This study aims to identify the possible "bottlenecks" where food is wasted in the University Restaurant (RU) of the Federal University of Santa Maria (UFSM) and propose measures that seek to reduce such waste. The subject is justified by the need to reduce costs in the public sector in order to continuously improve the quality of services, the sustainability of the planet and fighting hunger. To reach that goal, we used the methodology of case study, qualitative approach and descriptive. Data were collected through a questionnaire conducted during the year 2013, with users from the RU about the possible causes which impel them to leave remnants in the dishes. The results highlight the need for changes in the menu and change as preparing meals, providing plates and cups of different sizes and obligation in scheduling meals to reduce food waste in the RU.